Connecting Families and Character Education: Development of a Home-Visit Parenting Module for Children Aged 5–6 Years - Rohyana Fitriani; Miftahul Hidayati Syam; Lailatul Ismi; Rabihatun Adawiyah (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2026)
Purpose - Ineffective collaboration between parents and teachers and limited parental guidance remain challenges in developing character values among children aged 5–6 years. This study aimed to develop a parenting teaching module using a home visit approach to support early childhood character development. Design/methods/approach – This study employed a Research and Development (R&D) method adapted from Borg and Gall and simplified into seven stages: preliminary study, planning, initial product development, product validation, product testing, product revision, and implementation testing. Data were collected through observations, interviews, documentation, and structured Likert-scale questionnaires administered to media and material experts. The participants involved 12 children at TKIT Qolbun Salim. Findings – The findings showed that the developed module was highly feasible based on expert validation results. The implementation of the module improved children’s character and moral development, with the average achievement increasing from 45.16% to 82.5%. Individually, 33.3% of children developed as expected and 66.7% developed very well. Research implications/limitations – This study was limited by the small sample size and implementation in a single kindergarten setting, which may affect the generalizability of the findings. Originality/value – This study provides a home visit-based parenting teaching module as an alternative strategy to strengthen parental involvement and support character education in early childhood.